The Influence of Leadership Style on Employee Work Motivation - Pretty Novita Zai; Rizki Syafril (Al-Qalam Institue, 2025)
This study examines the impact of various leadership styles on work motivation within a government organization. The researcher used a quantitative method with an associative approach. Leadership style (X) acts as the independent variable, while work motivation (Y) is the dependent variable. The population consists of all employees, with 37 respondents selected as the sample. Information was collected using a Likert scale survey and analyzed using basic linear regression in SPSS version 25. The findings indicate that leadership style has a significant effect on employee work motivation, as indicated by a p-value of 0.000, which is below 0.05 (0.000 < 0.05), and a t-statistic of 8.421, which exceeds the t-table value of 2.030 (8.421 > 2.030). These findings confirm that leadership style has a significant impact on individual work motivation. These results also suggest that effective leadership practices can be strategically adopted in educational institutions to improve staff motivation and institutional performance.